Developing Learning Descriptive Text Materials To Support Literacy Skills through DeBeBino Game of the Seventh Grade Students of SMPN 2 Wonoayu - Masrukhah, Lilik (Jetlal, 2017)
This study purposed to develop language learning materials to support literacy skills of Seventh D grade students at SMPN 2 Wonoayu. Classroom Action Research design was employed in this study. The data were collected through document study, observation, questionnaire, and test. The findings show that the literacy coverage of English language learning for Seventh D grade students includes reading simple descriptive texts and writing simple and meaningful descriptive sentence. The rich language learning environment materials were developed in various texts such as topical vocabulary, grammar focus, everyday expression and language game, need to be developed. The quality of the developeddescriptive text material is good based on the result of the expert judgments and the result of questionnaires. The descriptive text material was effective to support Seventh D grade students’ literacy skills based on the result analysis on the literacy skills. The post-test result was significantly higher than the pre-test scores. Thus, the material is recommended to be used as supplementary material to support students’ literacy skills of seventh D grade at SMPN 2 Wonoayu.